The characteristics of current patterns in the waters of port of Tanjung Emas Semarang - ., Hartanto; Tjahjono, Agust; Sugiharto, Rudy (International Journal of Engineering and Technology, 2020)
The Port of Tanjung Emas Semarang is located in the northern of Java which is regarded as a strategic position to support sea transportation connectivity to Kalimantan. Conducted at the Port of Tanjung Emas Semarang, this research applied exploratory descriptive as the research methodology. Measurements of this research were made by using ADCP (Acoustic Doppler Current meter Profiler) type of Multi Cell Argounaut-XR. The research was carried out in 3 days (January 16th, 2016 â€“ January 19th, 2016). Current velocity data were taken at Â± 7 meters depth in five depth strata. The research was aimed to measure the current pattern and distribution of ballast water discharges from commercial vessels at the port. Based on the research, it was found that the current velocity of all water columns in the port varied ranging from 0.042-0.124 m/s with minimum current velocity of 0.0â€“0.003 m/s and maximum current velocity of 0.139-0.452 m/s. It was also found that the dominant current direction was north and south. It was predicted that the distribution of the ballast water discharges during falling tide (the tide went from high to low) moved from south to north, heading the port exit. In contrast, during rising tide (the tide went from low to high), the distribution of the ballast water discharges moved from north to south, heading the estuary of Baru river.Â Â